Regency Returns: Notes on Decoration - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses the revival of English Regency themes in home decoration. Describes the materials, colors, history, and idiosyncrasies of the English regency decorative style. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Interior decoration; Interior decoration--English influences